Organization of self-advantageous niche by neural stem/progenitor cells during development via autocrine VEGF-A under hypoxia - Taichi Kashiwagi; Yuuki Takazawa; Tetsushi Kagawa; Tetsuya Taga (BMC, 2023)
Abstract Background Tissue stem cells are confined within a special microenvironment called niche. Stem cells in such a niche are supplied with nutrients and contacted by other cells to maintain their characters and also to keep or expand their population size. Besides, oxygen concentration is a key factor for stem cell niche. Adult neural stem/progenitor cells (NSPCs) are known to reside in a hypoxic niche. Oxygen concentration levels are lower in fetal organs including brain than maternal organs. However, how fetal NSPCs adapt to the hypoxic environment during brain development, particularly before pial and periventricular vessels start to invade the telencephalon, has not fully been elucidated. Methods NSPCs were prepared from cerebral cortices of embryonic day (E) 11.5 or E14.5 mouse embryos and were enriched by 4-day incubation with FGF2. To evaluate NSPC numbers, neurosphere formation assay was performed. Sparsely plated NSPCs were cultured to form neurospheres under the hypoxic (1% O2) or normoxic condition. VEGF-A secreted from NSPCs in the culture medium was measured by ELISA. VEGF-A expression and Hif-1a in the developing brain was investigated by in situ hybridization and immunohistochemistry. Results Here we show that neurosphere formation of embryonic NSPCs is dramatically increased under hypoxia compared to normoxia. Vegf-A gene expression and its protein secretion were both up-regulated in the NSPCs under hypoxia. Either recombinant VEGF-A or conditioned medium of the hypoxic NSPC culture enhanced the neurosphere forming ability of normoxic NSPCs, which was attenuated by a VEGF-A signaling inhibitor. Furthermore, in the developing brain, VEGF-A was strongly expressed in the VZ where NSPCs are confined. Conclusions We show that NSPCs secret VEGF-A in an autocrine fashion to efficiently maintain themselves under hypoxic developmental environment. Our results suggest that NSPCs have adaptive potential to respond to hypoxia to organize self-advantageous niche involving VEGF-A when the vascular system is immature.